Evaluation of High-dose versus Standard-dose of Dexamethasone on Mortality among the Mechanically Ventilated COVID-19 Patients - Kale-Pradhan, Pramodini B.; Pacitto, Regina; Giuliano, Christopher A.; Johnson, Leonard B. (Current Drug Safety, 2024)
Introduction: Anti-inflammatory agents like dexamethasone (DEX) are a mainstay of treatment for COVID-19. Despite randomized trials demonstrating that a 6 mg daily dose of DEX improved patient outcomes in hospitalized COVID-19 patients receiving oxygen, clinicians often prescribe higher doses of corticosteroids without evidence to support this practice. The purpose of this study was to compare outcomes of ventilated COVID-19 patients who received standard dose (SD) versus high dose (HD) DEX. Methods: This was a multi-site, retrospective, observational study on ventilated COVID-19- positive patients who received DEX for at least three days between June 1, 2020, and January 31, 2022. The primary outcome of this study was the association between mortality and SD (<6 mg daily) versus HD (>10 mg daily) DEX in ventilated COVID-19 patients. Secondary outcomes included average blood glucose (BG), number of BG readings above 200, incidence of bacterial nosocomial infection, ventilator-free days, length of stay (LOS), and ICU LOS. Results: Of the 212 included patients, 53 (25%) received SD DEX, and 159 (75%) received HD DEX. There was no significant effect of DEX dose on mortality, number of BG readings >200, incidence of nosocomial infections, LOS, or ventilator-free days (p >0.05). After controlling for confounding factors, no difference in mortality persisted (OR 1.34 95% CI 0.62- 2.90). Average daily BG and ICU LOS were significantly greater in the HD group compared to the SD group (p = 0.003, p = 0.019, respectively). Conclusion: There was no association between HD DEX and mortality among ventilated COVID- 19 patients compared to SD DEX. Moreover, HD DEX is associated with detrimental effects such as prolonged ICU LOS and higher average daily BG. This study supports the use of SD DEX in ventilated COVID-19 patients.
Keywords: blood glucose